Charge Transport In Zirconium Doped Anatase Nanowires Dye-Sensitized Solar Cells: Trade-Off Between Lattice Strain and Photovoltaic Parameters - P. S. , Archana; Gupta, Arunava; M. M., Yusoff; Rajan, Jose (AIP Publishing LLC., 2014)
Zirconium (Zr) is doped up to 5 at. % in anatase TiO2 nanowires by electrospinning and used as working electrode in dye-sensitized solar cells. Variations observed in the photovoltaic parameters were correlated by electrochemical impedance spectroscopy, open circuit voltage decay, and X-ray diffraction measurements. Results show that homovalent substitution of Zr in TiO2 increased the chemical capacitance and electron diffusion coefficient which in turn decreased charge transport resistance and charge transit time. However, lattice strain due to size mismatch between the Zr4+ and Ti4+ ions decreased open circuit voltage and fill factor thereby setting a trade-off between doping concentration and photovoltaic properties.